2006
DOI: 10.1108/02686900710715611
|View full text |Cite
|
Sign up to set email alerts
|

Restoring public confidence in capital markets through auditor rotation

Abstract: PurposeTo determine the effect of audit firm rotation and/or audit partner rotation on individuals' confidence in the quality of audited financial statements.Design/methodology/approachTwo separate behavioral studies were conducted with participants from the business and legal community (MBA and law students). In each study, one‐way analysis of variance was conducted using a between‐subjects approach. The independent measure was auditor rotation; the dependent measure was participants' responses to questions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 15 publications
4
20
2
3
Order By: Relevance
“…Auditors in long-term assignments (more than 5 years) disapprove of a maximum accounting policy due to learning and experience effects (Myers et al (2003) ,826-38,794 US corporations between 1990and 2000, Ghosh and Moon (2005 show that investors, rating agencies and analysts assume positive interdependence between the duration of assignment and the quality of accounting, represented by the interest rate investors require, rating results, as well as the analysts' performance prognoses. Contrary to their results with US students on internal rotation, Gates et al (2007) show that investors' confidence in the financial accounting quality in a regulatory environment with increased Corporate Governance methods cannot be influenced by external auditor rotation. Furthermore, according to Carcello and Nagy (2004) based on the business years of 1990-2001, 267 US corporations showed balance manipulations mostly in the first 3 years of the assignment, since the management assumes lower quality of audit provided by new auditors.…”
Section: Decrease or Lack Of Proof Of Increasecontrasting
confidence: 74%
See 1 more Smart Citation
“…Auditors in long-term assignments (more than 5 years) disapprove of a maximum accounting policy due to learning and experience effects (Myers et al (2003) ,826-38,794 US corporations between 1990and 2000, Ghosh and Moon (2005 show that investors, rating agencies and analysts assume positive interdependence between the duration of assignment and the quality of accounting, represented by the interest rate investors require, rating results, as well as the analysts' performance prognoses. Contrary to their results with US students on internal rotation, Gates et al (2007) show that investors' confidence in the financial accounting quality in a regulatory environment with increased Corporate Governance methods cannot be influenced by external auditor rotation. Furthermore, according to Carcello and Nagy (2004) based on the business years of 1990-2001, 267 US corporations showed balance manipulations mostly in the first 3 years of the assignment, since the management assumes lower quality of audit provided by new auditors.…”
Section: Decrease or Lack Of Proof Of Increasecontrasting
confidence: 74%
“…Likewise for the Australian capital market Hamilton et al (2005) prove in 3,621 cases, observed during the business years of 1998-2003, that internal auditor rotation reduces accounting policy. According to Gates et al (2007) an experiment among US students shows that auditor rotation increases investors' confidence in the quality of financial accounting in a regulatory environment with increased corporate governance procedures. As one among few surveys, Zimmermann (2008) refers to the German capital market.…”
Section: Increasementioning
confidence: 99%
“…Gates, Lowe, and Reckers (2007) reported that even in an environment of strong corporate governance controls, audit firm rotation does not incrementally influence individuals' confidence in reported financial statements, measured as the assessed quality of a company's earnings.…”
Section: Geiger and Raghunandan (2002) Audit Report Preceding Bankruptcymentioning
confidence: 98%
“…Hal ini dikarenakan adanya praktik nyata, misalnya skandal Enron yang disebabkan oleh kegagalan audit oleh KAP Arthur Anderson, sehingga dikeluarkannya peraturan rotasi auditor dalam Sarbanes Oxley Act. Konsep rotasi pada level KAP akan memberikan manfaat bagi kua litas audit yang dilaksanakan oleh akuntan publik karena konsep ini akan membatasi kedekatan hubungan antara kantor akuntan public dan klien akibat dari tenur KAP yang terlalu lama (Gates et al 2007).…”
Section: Hasil Dan Pembahasanunclassified
“…Dimasukkannya ketentuan yang mewajibkan rotasi audit ke dalam Sarbanes-Oxley Act tidak terlepas dari pertimbangan bahwa terlalu lamanya pelaksanaan audit oleh auditor independen pada satu klien akan berpotensi menciptakan kedekatan (closeness) antara auditor bersangkutan dengan manajemen klien yang diauditnya. Kedekatan hubungan antara auditor dan klien diyakini berdampak negatif terhadap independensi, serta dapat mengurangi keandalan dan kualitas audit sehingga berkontribusi bagi terjadinya skandal-skandal keuangan di Amerika Serikat (Gates et al 2007). Peraturan terkait rotasi partner (rekan) audit di dalam Sarbanes-Oxley Act mendorong negara-negara lain untuk menerbitkan peraturan serupa, Kewajiban rotasi KAP dan partner audit juga merupakan salah satu ketentuan yang dimasukkan ke dalam UndangUndang tentang Akuntan Publik.…”
unclassified